Aspects of a Roman Bath at Argos - Sarri, Eleni (Rei Cretariae Romanae Fautorum Acta, 2015)
During the summer of 1994 and 1995, the 4th Ephorate of Prehistoric and Classical Antiquities at Nauplion carried out a rescue excavation1 on the plot of A. Yiakoumakis, at the southwest part of the modern city of Argos, in Peloponnese.